Factors the Development of Region Promotion Activities Centre (PKWp) in Lebak District Banten Province - Sierfi Rahayu; Hardi Warsono; Budi Puspo Priyadi (Jurnal Ilmiah Ilmu Administrasi Publik, 2019)
Lebak Regency as one of the districts that is still lagging behind in Banten Province, does not rule out the possibility of having the potential to be developed so that it can compete with other districts / cities in Banten Province. PKWp is the center of activities that are promoted later to be designated as Regional Activity Centers. There are two sub-districts included in the PKWp in Lebak Regency, namely Maja and Bayah. The problem that occurs is that it still relies on the agricultural sector so that it needs to be developed in the non-agricultural sector, limited supervision of spatial utilization, not yet supporting infrastructure facilities in the development of PKWp, and regional disparities between districts in Lebak Regency. The purpose of this study was to find out and analyze the development of PKWp in Lebak Regency and analyze the driving or inhibiting factors in developing PKWp in Lebak Regency. This study used qualitative research methods. The results of this study the driving factors in regional development, namely physical (education, health, economy and infrastructure) and investment, while inhibiting factors in regional development, namely social, productive population migration, government policies, trade patterns and trade activities.